Fortalecimiento de la gestión presupuestal. Estudio de caso: Secretaría Distrital de seguridad, convivencia y justicia de la Alcadía Mayor de Bogotá d.c. en el marco del plan de desarrollo distrital "Bogotá mejor para todos" - Rodrigues, António (2020)
This work pretends to analyze, propose and implement management tools, which allows follow-up and permanent monitory of the investment projects of the District Department of Security, cohabitation and justice. This instrument approaches from a data-based analysis and was taken from a management matrix of the current project investment budget coming from the relevant sections of the institution, hereinafter, we are going to identify the significant information of the Security, cohabitation and justice management resources investment required for executives and general citizens, and conclusively, the management tools suggested will be stablished and implement, hence, by announcements and reports related to the security, cohabitation and justice financial resources use, which makes easier not only the decision making, but the outreach of the institutional budgetary management. The main purpose of this investigation is to improve the investment management of the District Department of Security, cohabitation and justice, sharing relevant information which contributes to the effective decision making, to ensure a higher impact on the city safety and justice indicators.